Polyclonal endemicity of Pseudomonas aeruginosa in a teaching hospital from Brazil: molecular typing of decade-old strains - Fortaleza, Carlos Magno Castelo Branco [UNESP]; Bacchi, C. E. [UNESP]; Oliveira, Deilson Elgui de [UNESP]; Ramos, M. C. (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
Pseudomonas aeruginosa infections cause significant mortality and morbidity in health care settings. Strategies to prevent and control the emergence and spread of P. aeruginosa within hospitals involve implementation of barrier methods and antimicrobial stewardship programs. However, there is still much debate over which of these measures holds the utmost importance. Molecular strain typing may help elucidate this issue. In our study, 71 nosocomial isolates from 41 patients and 23 community-acquired isolates from 21 patients were genotyped. Enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) was performed. Band patterns were compared using similarity coefficients of Dice, Jaccard and simple matching. Strain similarity for nosocomial strains varied from 0.14 to 1.00 (Dice); 0.08 to 1.00 (Jaccard) and 0.58 to 1.00 (simple matching). Forty patterns were identified. In most units, several clones coexisted. However, there was evidence of clonal dissemination in the high risk nursery, neurology and two surgical units. Each and every community-acquired strain produced a unique distinct pattern. Results suggest that cross transmission of P. aeruginosa was an uncommon event in our hospital. This points out to a minor role for barrier methods in the control of P. aeruginosa spread.
Keywords: Pseudomonas aeruginosa; strain typing; ERIC-PCR; nosocomial infections; health care infections